Research hub: increasing university visibility towards global prominence - Saiyed Yeop, Sharifah Fahimah; Mustaffa, Maria Hani; Hassan, Mohd Mokrim; Haron, Muhammad Firdaus (Universiti Teknologi MARA, Kedah, 2018)
The Research Hub project aimed to produce the platform of knowledge – technology centric. It comprises of multiple services in a single platform, i.e. research publications, researchers community engagement, university collaboration, research blogs, and the major component in Research Hub is the content search engine. Method/Approach: The approach applies in this project are, first, the desktop benchmarking with the universities that were implement the research hub concept to strengthen research services. Second, the major library and information science journal and databases had been examined to get clear understanding on the concept of research hub. Third, the example of open source system had been tested and series of study and comparison on their features, specification and capabilities to fit the requirement of the hub. And finally, the development model of Research Hub as the next generation library services been developed, tested and implemented in the university. Findings: Research Hub for the geosciences and petroleum engineering scope are among the pioneer hub that had been rolled out for the six month. Based on the findings and feedback from the research community and student, the concept and implementation of Research Hub had been upgraded into the research institutes gateway. The portal had boost up the visibility of the university publications through search engine optimization for three folds in six months. Originality/Values: Research Hub, is the product of Library 4.0 concept which applies the element of collaboration, open source, ubiquitous web, massive data and intelligent based agent. The study and development of Research Hub model are significant for deriving the next generation library services in realizing sustainable development goals 2030. Novelty and Uniqueness: Originality/Values: Research Hub, is the product of Library 4.0 concept which applies the element of collaboration, open source, ubiquitous web, massive data and intelligent based agent. The study and development of Research Hub model are significant for deriving the next generation library services in realizing sustainable development goals 2030.